Volumes cortical e subcortical como preditores do desempenho cognitivo em alcoolistas : um estudo de seguimento de 6 anos - Morgado, Adriano Daniel Peres (2017)
Alcohol use has been long proven to result in brain atrophy and cognitive deficiencies, but how changes of specific brain structures would be related to these cognitive changes remains unclear. This study explored changes of gray matter cortical and subcortical volumes of alcoholics after 6-years interval and their relation to changes of frontal executive and global cognitive mental status. Cortical and subcortical segmentation and corrections of magnetic resonance (1.5 T) images acquired in 2010 (T1) and 2016 (T2) from 16 alcoholics (14 males, mean age 49.8 years ± 8.5 SD in T1 and 55.7 years ± 8.4 SD in T2) with long-term use of alcohol (mean of 29.8 to 34.7 years) were performed using FreeSurfer. Results showed global reduction of gray matter volumes and more specifically in brain regions, mostly from prefrontal areas, subcortical structures and cerebellum cortex, highly related to the executive function and drug dependence condition. More importantly, reduction over the 6-year interval of gray matter volumes of right frontal pole (p < .01) and left cerebellar cortex (p < .05) were predictive of changes of frontal executive performance, and reduction of right putamen gray matter volume was predictive (p < .05) of changes of global cognitive mental status in alcoholics. We suggest that combination of volumetric analysis of gray matter from specific brain areas with brief examination of frontal executive and global cognitive mental status over the course of alcohol use may be clinically relevant to determine the degree of executive and cognitive commitment in alcoholism.